2022
DOI: 10.1111/jsr.13770
|View full text |Cite
|
Sign up to set email alerts
|

The association between social jetlag and parameters of metabolic syndrome and type 2 diabetes: a systematic review and meta‐analysis

Abstract: This study aims to determine the association between social jetlag and parameters of metabolic syndrome and type 2 diabetes (T2D) in a systematic review and meta-analysis.A systematic literature search was conducted in PubMed/Embase/Scopus until May 2022. Included studies described an association between social jetlag and parameters of the metabolic syndrome and/or T2D, were available full text and written in English or Dutch. Data extraction and quality assessment were performed on pre-piloted forms independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…Overall, our results show that social jet lag is associated with several glycemic and metabolic markers. Previous research has supported these findings, as our recent meta-analysis showed that social jet lag was significantly associated with higher BMI, waist circumference, HbA1c levels, and systolic blood pressure in general but also in people with diabetes [7]. This is also in agreement with findings in people with type 1 diabetes [8][9][10][11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our results show that social jet lag is associated with several glycemic and metabolic markers. Previous research has supported these findings, as our recent meta-analysis showed that social jet lag was significantly associated with higher BMI, waist circumference, HbA1c levels, and systolic blood pressure in general but also in people with diabetes [7]. This is also in agreement with findings in people with type 1 diabetes [8][9][10][11].…”
Section: Discussionsupporting
confidence: 89%
“…Our recent meta-analysis of the associations among social jet lag and parameters of the metabolic syndrome and T2D has shown that social jet lag is associated with increased levels of glycated hemoglobin (HbA1c), higher body mass index (BMI), higher waist circumference, and higher odds of obesity [7]. Social jet lag has also been associated with worse glycemic control, higher HbA1c levels, and higher insulin requirements in people with type 1 diabetes [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas our study did not find a significant association between social jetlag and the risk of metabolic syndrome, 1–2 h of social jetlag was linked to a reduced risk of metabolic syndrome among non-shift workers after additional adjustment for the interaction between shift work and social jetlag. Earlier studies reported that higher social jetlag was associated with an increased likelihood of higher waist circumference, a component of metabolic syndrome [ 38 , 39 ]. One plausible reason for this result may be the comprehensive adjustment for various factors in our analysis, including shift work status, sleep duration, and the interaction between social jetlag and shift work as a potential confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant associations were observed for T2D development. 25 Overall, limited to no evidence has been found on the role of (maternal) sleep (duration or quality) as well as circadian disturbance in the development of T1D. A prospective observational study found an association of sleep initiation and maintenance with adult-onset autoimmune diabetes (hazard ratio 95% CI 1.01-2.22), but there were only a limited number of people with "classical" T1D in this group.…”
Section: Circadian Rhythmmentioning
confidence: 93%
“…60 Finally, also in our meta-analysis we showed that social jetlag was associated with suboptimal glycemic (ie, glucose) and metabolic outcomes (ie, hypertension) in people with diabetes (both types). 25…”
Section: Circadian Rhythmmentioning
confidence: 99%